Volume 89A, Number 6, June 2016 Cover Image. Issue 6 (June 2016) - Unknown
Abstract: On the cover: Like the universe around us, the human body does not extend just in space, but in space‐time. Our bodies age at different speeds with gender, among other innate and environmental factors, challenging biomedical researchers to create standardized strategies for detection of age‐ and gender‐dependent differences in clinical patient samples. Read the accompanying article by Kverneland and coworkers in this issue of Cytometry Part A. Cover design by Bärbel Beran [www.beran‐design.de ].